Implementation of the Subsidized Fertilizer Program for Subak in West Selemadeg District, Tabanan Regency, Bali Province - I Wayan Agung Hardita; I Made Sudarma; Ratna Komala Dewi (Journal of Sustainable Development Science, 2024)
The government facilitates various agricultural facilities and infrastructure as an effort to increase food productivity, one of which is by implementing a fertilizer subsidy policy. The realization of subsidized fertilizer redemption in West Selemadeg District in 2023 is still not effective. The aim of the research is to analyze the implementation of the subsidized fertilizer program in West Selemadeg District, Tabanan Regency, Bali Province by analyzing farmers' perceptions of subsidized fertilizer policies, and analyzing the effectiveness of subsidized fertilizer distribution.. The sample in this study consisted of 68 farmers. The data analysis used is Likert Scale analysis. The results of the research showed that farmers' perceptions of the subsidized fertilizer policy in West Selemadeg District were in the good category and the effectiveness of subsidized fertilizer distribution in West Selemadeg District was in the fair category.